Effects of sera taken from women with recurrent spontaneous abortion on sperm motility and apoptosis - Tahereh Talaei-khozani; Zahra Borzoei; Soghra Bahmanpour; Jaleh Zolghadr; Sedigheh Dehbashi; Hamid Reza Zareh (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2011)
Background: Recurrent spontaneous abortion impacts almost 1% of couples. The sera from women with unexplained recurrent spontaneous abortion (URSA) have toxic effects on embryos that grow in the uterus. Therefore, the abnormal condition of the uterus may also affect sperm qualities.Objective: The objectives of this study were to search if these sera could induce DNA denaturation in sperm nuclei and also it could reduce sperm motility.Materials and Methods: Sera of 20 women with URSA history and sera from 20 women with at least two healthy children were added to the sperms samples from 20 healthy men for 2 hours. The sperm motility was assessed after incubation with sera. The samples were stained with Tdt mediated dUTP nick end labeling (TUNEL) assay for DNA fragmentation. The samples were analyzed with flow cytometry and the percentage of the TUNEL positive sperms were calculated. The data were analyzed by t-test.Results: The incubation of the sperm samples in sera with URSA lead to a decrease in the percentage of the motile sperm from 55% in control to 41% in the treated group, significantly (p=0.038). The percentage of the sperm with abnormal fragmented DNA increased after incubation with URSA (26.6%) compare to the control (21.2%); however, it was not significant.Conclusion: It seems that sera from URSA patients could not induce a significant increase in the percentage of the sperms with nuclei contain DNA fragmentation. However, the sera of women with URSA could affect the fertility rate by reduction of the sperm motility.